Belonging to Socially Excluded Groups as a Predictor of Vaccine Hesitancy and Rejection - Eshel, Yohanan; Kimhi, Shaul; Marciano, Hadas; Adini, Bruria (Frontiers in Public Health, 2022)
The scientific call for vaccination against the COVID-19 pandemic has met hesitancy, postponement, and direct opposition of parts of the public in several countries. Mistrusting the COVID-19 vaccine, distrusting the authorities, and unrealistic optimism, are three major reasons employed in justifying vaccine hesitancy. The present study examines two major issues. First, it strives to identify individuals that are unwilling to adhere to the vaccination process, more strongly question the effectiveness and necessity of the COVID-19 vaccine, and wonder about potential covert reasons for its administration. Second, it investigates associations between such ‘conspiracy’ claims and the actual rejection of the vaccine. We assume that individuals belonging to social groups which are partly excluded by the general society, will be less willing to fulfill the demands of this society, more inclined to reject the vaccine and associate it with some hidden conspiracy. A relatively large sample of the Israeli public (N = 2002) has responded to an anonymous questionnaire pertaining, among other things, to vaccine hesitancy and to the individual level of vaccine uptake. Previous research has mainly examined the reasons for vaccine hesitancy. The present study’s results indicate that three out of four social exclusion criteria (young adulthood, low level of income, and orthodox religiosity) have negatively predicted vaccine uptake and positively predicted three types of reasoning for vaccine hesitancy. Young adulthood was the strongest predictor of vaccine rejection. Attempts at convincing hesitating individuals to uptake this vaccine have often failed in many countries. As varied reasons underlie vaccine refusal, it is suggested that the approach to different vaccine rejecting groups should not be generic but rather tailor-made, in an attempt to influence their perceptions and behavior.